NDC Schemes and the Labor Market : Issues and Options - Holzmann, Robert; Robalino, David; Winkler, Hernan (World Bank, Washington, DC, 2019)
Defined contribution (DC) schemes whether unfunded or funded are often considered superior to defined benefit (DB) schemes in their ability to address labor market issues, particularly in encouraging formal employment and delayed retirement. Conceptually, the assessment is based on superior incentives to work and save. Yet economic and social realities are more complex. This paper explores design and labor market conditions that potentially constrain DC schemes. The paper concludes that to achieve their conceptual potential, DC schemes require design innovations, including a better integration of basic provisions and complementary labor policies that promote job creation in the formal sector and expand job opportunities during old age.